The analysis of approaches for the functional modeling of information systems - Шендрик, Віра Вікторівна; Бойко, Андрій Олександрович; Бондар, Олександр В’ячеславович (Technology audit and production reserves, 2015)
In this paper it is formulated the problem of integration of information systems in modern industrial enterprises. It was defined the basic classes of used information systems. Among these there are 3 classes: accounting, planning and economic class and IS of supporting production process (MES). The latter was chosen for detailed consideration as the least narrow scope. Analysis of approaches used during functional simulation of IP of MES-class in order to choose the most contemporary approach to build a functional model of information system of MES class of manufacture that is not specialized in the development of IS. Because of the requirement for sufficient formalized reflect the processes that occur during the operation were formed quantitative and qualitative criteria against which the effectiveness was compared to models created by the process and functional approaches. In a detailed analysis of these two approaches were identified their main advantages and disadvantages. Modeling a model of the system using the process approach can increase the versatility of information systems of MES class at the design stage, through its concentration on the final result and optimal method for achieving it. At the same time the advantage of using a functional approach due to lower cost that are necessary to develop a functional model. Thus, recommendations are proved for further functional modeling of information systems of MES class use process approach.